The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.30935/cedtech/11479
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perception About MOOCs and ICT During the COVID-19 Pandemic

Abstract: Technological advances such as Massive Open Online Courses (MOOCs) and Information and Communication Technologies (ICT) allow the construction of new spaces where students consult the information at any time, take the online exams and communicate with the participants of the educational process from anywhere. This quantitative research analyzes the perception of the teachers about the organization of the school activities in MOOCs and use of ICT considering machine learning and decision tree techniques (data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…However, we also found tensions between teacher perception of educational planning policies and the direction for which these policies had been planned. This is consistent with existing literature (e.g., Merga et al, 2021;Salas-Rueda et al, 2022). Teacher perception and practices are in nature in complex, fostered by different ideological, political, economic, and sociocultural affordances (Gao, 2021b) even in normal times.…”
Section: Tensions Between Teacher Beliefs and Practicessupporting
confidence: 91%
“…However, we also found tensions between teacher perception of educational planning policies and the direction for which these policies had been planned. This is consistent with existing literature (e.g., Merga et al, 2021;Salas-Rueda et al, 2022). Teacher perception and practices are in nature in complex, fostered by different ideological, political, economic, and sociocultural affordances (Gao, 2021b) even in normal times.…”
Section: Tensions Between Teacher Beliefs and Practicessupporting
confidence: 91%
“…Various authors (e.g., Salas-Rueda, 2021;Salas-Rueda et al, 2022) have used data science to understand the use of technological tools in the educational field. For example, the RapidMiner tool allowed calculating the linear regressions (machine learning) to evaluate the research hypotheses through the training section (70%, 80% and 90% of the sample).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from that, they expressed that they are willing to acquire more ICT knowledge [22] and they portrayed their intentions to apply technology after the barrier of pandemic is ceased later [40]. It is undeniable that the disruption of COVID-19 outbreak could be considered as one step forward to a new educational paradigm as teachers were driven to pick up the ICT skills to conduct teaching and learning sessions online, and most probably teachers realize that using technology in teaching and learning persistently may influence students' motivation, participation and learning in a positive manner [46]. In contrast, previous studies [36], [43] showed that teachers portrayed a moderate level of technology acceptance as they were not ready to conquer the challenges of emergency remote teaching yet.…”
Section: Teachers' Technology Acceptance Level For Emergency Remote T...mentioning
confidence: 99%